2015
DOI: 10.1161/circulationaha.114.012805
|View full text |Cite|
|
Sign up to set email alerts
|

Endovascular Versus External Targeted Temperature Management for Patients With Out-of-Hospital Cardiac Arrest

Abstract: Background— Targeted temperature management is recommended after out-of-hospital cardiac arrest. Whether advanced internal cooling is superior to basic external cooling remains unknown. The aim of this multicenter, controlled trial was to evaluate the benefit of endovascular versus basic surface cooling. Methods and Results— Inclusion criteria were the following: age of 18 to 79 years, out-of-hospital cardiac arrest related to a presumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 40 publications
7
97
0
1
Order By: Relevance
“…Similar to the Italian study [17], 36% of our respondents cited lack of equipment as the reason for not using TTM. There is no contraindication for using TTM without specific equipment; despite more precise temperature control, reduced latency in reaching the target temperature (when 32-34°C is chosen as the target), and less nursing staff workload, there is no evidence of better patient outcomes when using dedicated equipment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Italian study [17], 36% of our respondents cited lack of equipment as the reason for not using TTM. There is no contraindication for using TTM without specific equipment; despite more precise temperature control, reduced latency in reaching the target temperature (when 32-34°C is chosen as the target), and less nursing staff workload, there is no evidence of better patient outcomes when using dedicated equipment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…One study found good neurological outcomes of 35.4 versus 25.6 % for endovascular versus surface cooling [46]; another, of 45 versus 38 % [47]. Recently, the results of a prospective multicenter RCT in 400 patients comparing endovascular to basic surface cooling methods have been published [48]. The authors observed significantly shorter time to target temperature, fewer cases of overshoot, more effective temperature control during maintenance and re-warming, reduced nursing workload, and a trend to better outcome at 90 days (34.6 vs. 26.0 %, OR 1.51 [0.96-2.35], p = 0.07) with endovascular cooling [48].…”
Section: Start Temperature Managementmentioning
confidence: 99%
“…Recently, the results of a prospective multicenter RCT in 400 patients comparing endovascular to basic surface cooling methods have been published [48]. The authors observed significantly shorter time to target temperature, fewer cases of overshoot, more effective temperature control during maintenance and re-warming, reduced nursing workload, and a trend to better outcome at 90 days (34.6 vs. 26.0 %, OR 1.51 [0.96-2.35], p = 0.07) with endovascular cooling [48]. It is unclear whether these differences were due to the specific cooling technologies used, or (more likely) to greater efficacy and accuracy of temperature control, especially during maintenance and re-warming [49].…”
Section: Start Temperature Managementmentioning
confidence: 99%
“…Now there is compelling new evidence on this issue from a study by Deye and coworkers, 20 who compared endovascular with surface cooling in a prospective, multicenter RCT, the results of which are published in this issue of Circulation. The authors enrolled 400 patients; 203 were treated with endovascular cooling (using Zoll femoral Icy catheters) and 197 were treated with external cooling (ice packs, fans, and a homemade tent).…”
mentioning
confidence: 99%
“…The main findings were as follows: significantly shorter time to target temperature (33.0°C), greater stability of temperature (defined as time within target ±1°C) in the maintenance phase, and reduced nursing workload (10 versus 38 minutes, P<0.001) in the endovascular group; more minor side effects (likely attributable to more effective cooling) in the endovascular group (P=0.009); a nonsignificant trend toward more favorable outcome at 28 days (36.0 versus 28.4%, odds ratio 1.41 [0.93-2.16], P=0.107; for shockable rhythm 53.7% versus 37.1%, odds ratio 1.97 [0.99-3.9], P=0.269) and at 90 days (34.6% versus 26.0%, odds ratio 1.51 [0.96-2.35], P=0.07) in the endovascular group; and fewer cases of severe overshoot (below 30°C) in the endovascular group (n=0 versus n=3). 20 Of note, strict fever control was maintained for a minimum of 3 days following rewarming in both groups. This is the first major study to directly compare the 2 fundamental cooling methodologies, ie, surface versus core cooling, in a prospective RCT; the authors are to be congratulated.…”
mentioning
confidence: 99%